H2O2 repurposes plant O2 sensing to regulate post-hypoxia responses - Salma Akter; Monica Perri; Mikel Lavilla-Puerta; Sophie Lichtenauer; Yuming He; Vinay Shukla; Laura Dalle Carbonare; Yuri Telara; Daai Zhang; Beatrice Ferretti; Dona M. Gunawardana; William K. Myers; et al. (Nature, 2026)
Abstract Understanding plant molecular responses to flooding is crucial for strategies to increase resilience. Plants respond to submergence-induced low oxygen (hypoxia) through decreased plant cysteine oxidase (PCO) activity, which stabilizes group VII ethylene response factors (ERFVIIs), master regulators of metabolic and anatomic acclimation responses 1–4 . Rapid reoxygenation on desubmergence induces a burst of reactive oxygen species (ROS) generation and metabolic reconfiguration 5,6 ; however, how plants mitigate this post-hypoxic stress to facilitate submergence recovery has remained unknown. Here we report that ERFVIIs are also important in post-submergence recovery, remaining stable upon reoxygenation through ROS-mediated PCO inhibition. Stabilized ERFVIIs are retained at hypoxia-responsive promoters, becoming repressors of typical hypoxia marker genes but upregulators of genes involved in ROS homeostasis and oxidative stress protection. Our findings suggest that PCOs and ERFVIIs integrate signals from both oxygen and ROS to coordinate ERFVII stability through submergence-induced hypoxia and desubmergence stress to promote plant survival and recovery.